Murder in the Manor (A Lacey Doyle Cozy Mystery-Book 1) - Fiona, Grace (Lukeman Literary, 2019)
MURDER IN THE MANOR (A LACEY DOYLE COZY MYSTERY-BOOK 1) is the debut novel in a charming new cozy mystery series by Fiona Grace. Lacey Doyle, 39 years old and freshly divorced, needs a drastic change. She needs to quit her job, leave her horrendous boss and New York City, and walk away from the fast life. Making good on her childhood promise to herself, she decides to walk away from it all, and to relive a beloved childhood vacation in the quaint English seaside town of Wilfordshire. Wilfordshire is exactly as Lacey remembers it, with its ageless architecture, cobblestone streets, and with nature at its doorstep. Lacey doesn't want to go back home-and spontaneously, she decides to stay, and to give her childhood dream a try: she will open her own antique shop. Lacey finally feels that her life is taking a step in the right direction-until her new star customer turns up dead. As the newcomer in town, all eyes are on Lacey, and it's up to her to clear her own name. With a business to run, a next-door neighbor turned nemesis, a flirty baker across the street, and a crime to solve - is this new life all that Lacey thought it would be? Book #2 in the series-DEATH AND A DOG-is also available for preorder!
Keywords: Krimi, detektivky